Does a progressive PIT stabilize the economy? A comparison of progressive and flat taxes - Piotr Krajewski; Katarzyna Piłat (Comparative Economic Research. Central and Eastern Europe, 2017)
The aim of the article is to examine the impact of progressive personal income tax rates and the effectiveness of this tax as an automatic economic stabilizer. The assessment of automatic stabilizers is based on the estimates of tax cyclical components. The study shows that the output elasticity of PIT is higher than one, which means that the analysed tax acts relatively efficiently as an automatic stabilizer. However, it was also observed that the tax progressivity is not the main reason of the effectiveness of a progressive PIT as an automatic stabilizer. The study shows that changes in progressive rates of PIT, contrary to widespread opinions, have little effect on the effectiveness of passive fiscal policy. Personal income tax acts as automatic stabilizer mostly due not to the progressive tax rates, but because of the sensitivity of employment to GDP fluctuations.
Keywords: 330; PIT; taxes; automatic stabilizers; fiscal policy